Case report: BRAF-inhibitor therapy in BRAF-mutated primary CNS tumours including one case of BRAF-mutated Rosai-Dorfman disease - Cronin, Christopher; McLaughlin, Ronan; Lane, Louise; Brett, Francesca M.; Jansen, Michael; Bermingham, Niamh; Wyse, Gerald; Grogan, Liam; Morris, Patrick G.; O’Reilly, Seamus (Frontiers in Medicine, 2022)
BRAF V600E oncogene mutations have been reported in multiple central nervous system (CNS) tumour types, and emerging evidence supports the use of targeted therapy in BRAF-mutated gliomas. BRAF oncogene mutations have recently been identified in Rosai-Dorfman Disease (RDD) – a rare non-Langerhan’s Cell histiocytosis. This series describes 3 patients from 2 neurosurgical centres in Ireland with BRAF V600E-mutated CNS tumours. Patients include a 19-year-old male with ganglioglioma with anaplastic features, a 21-year-old male with CNS involvement of Rosai-Dorfman Disease, and a 28-year-old female with ganglioglioma with anaplastic features . 2 patients received radiation with concurrent temozolomide prior to BRAF-targeted therapy. This case series describes clinical and radiological responses to BRAF-targeted therapy in BRAF V600E-mutated gliomas across multiple tumour grades, as well as only the second published report of response to targeted therapy in BRAF-mutated RDD. Durability of disease control with BRAF-targeted therapy was generally superior to that achieved with chemoradiation; one patient has experienced ongoing disease control for 5 years. The reported case of treatment response in BRAF-mutated RDD lends support to the strategy of genotyping and utilisation of targeted therapy in this rare disease. The optimal sequencing of BRAF-targeted therapy in BRAF-mutated gliomas/glioneuronal tumours remains unclear and further prospective studies are required to guide the use of genome-matched therapy in this patient population.